Chromatin modifications associated with activation and repression of stevor multigene family of plasmodium falciparum during the trophozoite stage - Mushunje, Annals Tatenda (2016)
The stevor multigene family is one of three gene families (including var and rifin) postulated to play a role in antigenic variation in Plasmodium falciparum. Recent work has shown how the protein is involved in cytoadherence, rosetting and possibly merozoite invasion showing the proteins involvement in the pathology of malaria. The parasite has 35+ stevor genes and expresses 1-3 of these at a parasite level. This tight level of gene control is not unique to stevor but to the vars and rifins as well. In this study, we aimed to characterize histone modifications associated with transcription activation and repression of stevor using ChIP-qPCR. We studied four stevors: a transgenic hdhfr-gfp stevor and three stevors expressed naturally. Our study shows that different stevor genes show histone-specific regulation and subtle differences in their regulation. H3/H4 acetylation reactions are involved in activation of stevor genes and are primarily enriched in the 5’ UTR as well coding regions of all stevors. H3K4 methylation reactions likely play a supporting role in activation of stevors and are enriched in stevor specific positions along the 5’ UTR and coding regions. H3K9/36 trimethylation reactions are enriched in the 3’ end of the 5’ UTR and coding regions and are involved in silencing. Interestingly we observed subtle differences between the epigenetic landscape of the stevors and we propose that the subtle differences observed between the epigenetic landscapes of the stevors, could in turn influence the transcription pattern of stevors and also could explain why stevors do not follow a strict mutual exclusion as observed for var genes.